AN ANALYZING METHOD THAT CAN BE FOLLOWED FOR THE EVALUATION OF THE LOCATION OF URBAN FACILITY AREAS - Hamamcioglu, Cenk; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, 2011)
For the evaluation of the location of urban facility areas; the institutional data and internal (employee) point of views are critically important. This article covers the definition of followed methodology in the surveys and the valuation method for the achieved information that is applied in the doctorate research named as 'The Evaluation of the Effects of Transportation Network on the Location of Urban Facilities in the Case of Istanbul Historical Peninsula'. The application of survey technique is adopt in principle during the collection of the institutional data and employee point of views. These surveys are implemented totally to the six administrative institutions which are stated precisely in order to constitute samples for the urban facility areas in 2008. Achieved information and data are gathered and transferred to SPSS / PC 15.0 (Statistical Package for Social Sciences) program. The variables submitting in the survey questions of options analyzed according to the frequency distribution.
Keywords: Urban facility; survey technique; frequency distribution; Engineering